EFEK APOMORFIN SUBLINGUAL PADA EREKSI PENIS - Salossa, Kaleb D.S.; Kalangi, Sonny J.R.; Adam, Ghazaly (Jurnal Biomedik : JBM, 2012)
Abstract: Erectile dysfunction is the disability of a male to maintain consistant or repeated penile erections sufficiently for successful sexual intercourse. Many efforts have been done to handle this condition, so far. The psychosocial therapy and several medications inter alia: testosterone, yohimbine, trazadone, direct intracavernosus injection of alprostadil, penile implantation, and  sildenafil citrate, are not always suitable for the patients’ needs, especiallly those who suffer from cardiovascular diseases. Therefore, a new erectogenic agent has been introduced, the sublingual apomorphine. This apomorphine has a dopamine-like molecule that acts on the dopamine receptors in the paraventricular nucleus (PVN) of the central nervous system to increase the penile erection due to sexual stimulation (erotic imagination, audiovisual, or tactile). The sublingual apomorphine has been proved effective in overcoming the erectile dysfunction, especially the mild and moderate forms. Keywords: penile erection, sublingual apomorphin.     Abstrak: Telah banyak upaya dilakukan untuk mengatasi disfungsi ereksi yang merupakan ketidakmampuan seorang laki-laki secara konsisten atau berulang untuk mencapai dan mempertahankan ereksi penis yang cukup untuk melakukan hubungan seksual. Terapi psikososial dan pengobatan yang pernah diajukan seperti pemberian hormon testosteron, yohimbin, trazadon, injeksi langsung alprostadil intrakavernosa, implantasi penis serta sildenafil sitrat tidaklah selalu sesuai dengan kebutuhan penderita, khususnya penderita disfungsi ereksi dengan penyakit kardiovaskuler. Para ahli berusaha melakukan terobosan baru salah satunya adalah apomorfin sublingual yang merupakan agen erektogenik baru. Apomorfin adalah suatu molekul mirip dopamin yang bekerja pada reseptor dopamin pada paraventricular nucleus (PVN) di sistem saraf pusat untuk meningkatkan rangsangan erektil saat stimulasi seksual (imaginasi erotik, audiovisual dan perabaan) terjadi. Apomorfin sublingual terbukti efektif untuk mengatasi disfungsi ereksi, terutama disfungsi ereksi ringan dan sedang. Kata kunci: ereksi penis, apomorfin sublingual.